Hubungan Masa Kerja Bidan dengan Kelengkapan Imunisasi Dasar pada Masa Pandemi Covid-19 - Hairiana Kusvitasari; Putri Yuliantie; Istiqamah (HEALTH CARE: JURNAL KESEHATAN, 2023)
The COVID-19 pandemic has disrupted health systems around the world and impacted immunization systems. One of the factors that can affect the completeness of basic immunization is the work period of midwives as immunization officers. This study aims to determine the relationship between tenure of midwives and completeness of basic immunization during the COVID-19 pandemic. Cross-sectional analytic survey research using an online questionnaire in the form of a Google form distributed through the WhatsApp group. The sampling technique used a total sampling of 34 midwives in 4 selected health centers according to the inclusion and exclusion criteria. The analytical method uses univariate and chi square. The results of this study were that there was no significant relationship between years of service in providing immunization services and the completeness of basic immunization during the COVID-19 pandemic in Bantul Regency with a p value of 0.25. Midwives are expected to optimize the performance of cadres in collecting infant data and using online media to conduct immunization counseling and carry out sweeping to monitor babies who have not received basic immunizations on a regular basis during the COVID-19 pandemic. Keywords: Working Period, Completeness of Basic Immunization, COVID-19